2008
DOI: 10.1093/scan/nsn036
|View full text |Cite
|
Sign up to set email alerts
|

On the neural control of social emotional behavior

Abstract: It is known that the orbitofrontal cortex (OFC) is crucially involved in emotion regulation. However, the specific role of the OFC in controlling the behavior evoked by these emotions, such as approach-avoidance (AA) responses, remains largely unexplored. We measured behavioral and neural responses (using fMRI) during the performance of a social task, a reaction time (RT) task where subjects approached or avoided visually presented emotional faces by pulling or pushing a joystick, respectively. RTs were longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
161
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(187 citation statements)
references
References 59 publications
26
161
0
Order By: Relevance
“…As evidence of this, Marsh et al (2005) found that participants were faster to push a joystick (''avoidance'') than to pull a joystick (''approach'') in response to angry faces by a difference of 65 ms. Similar effects have been found by Roelofs et al (2009a), Volman et al (2011), (Von Borries et al 2012, Seidel et al (2010), and also-in a group of socially anxious individuals-by Heuer et al (2007). However, conflicting results exist in the literature, as some researchers have found facilitation of approach behaviors toward fearful faces (Marsh et al 2005) and toward angry faces (Adams et al 2006).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…As evidence of this, Marsh et al (2005) found that participants were faster to push a joystick (''avoidance'') than to pull a joystick (''approach'') in response to angry faces by a difference of 65 ms. Similar effects have been found by Roelofs et al (2009a), Volman et al (2011), (Von Borries et al 2012, Seidel et al (2010), and also-in a group of socially anxious individuals-by Heuer et al (2007). However, conflicting results exist in the literature, as some researchers have found facilitation of approach behaviors toward fearful faces (Marsh et al 2005) and toward angry faces (Adams et al 2006).…”
Section: Introductionsupporting
confidence: 60%
“…In fact, a number of recent studies have used the approachavoidance methodology to assess automatic influences of task-irrelevant stimulus features on performance. Roelofs et al (2009a) performed a control experiment, whereby they adopted a gender identification task in which subjects had to perform push/pull movements in response to the gender of a face (male/female). Importantly, the faces were either smiling, or they were angry.…”
Section: Introductionmentioning
confidence: 99%
“…Some emotional facial expressions are thought to elicit overlearned action tendencies either to act or refrain from acting, or to approach or withdraw [48,49] -forms of reflexive post-stimulus control. In young adults, a region of lateral OFC has been found to be active when a required response (e.g., withdraw) is incongruent with the action tendency signaled by a previously presented face (e.g., smiling).…”
Section: Affective Tuning Can Shift With Age and Contextmentioning
confidence: 99%
“…In the second behavioural and psychophysiological session, a probabilistic reversal learning task (Den Ouden et al, 2013) and fear conditioning retention test are administered, to test cognitive flexibility and fear retention from the previous fear-conditioning task, respectively. Finally, during the second fMRI session, (neural) control over emotional actions is investigated with an approach–avoidance task (Roelofs, Minelli, Mars, Van Peer, & Toni, 2009), and resting-state scans are obtained before and after stress induction (Vogel et al, 2015), to assess stress-related alterations in resting-state networks. Saliva samples for endocrinological analyses are collected before the second MRI session, and at several time-points before and after the stress induction to assess stress reactivity.…”
Section: Methodsmentioning
confidence: 99%
“…To test whether (development of) PTSD symptoms is associated with reduced (neural) control over automatic action tendencies to approach positive (happy) and avoid negative (angry) emotional faces, we administer the approach–avoidance task (AAT) during functional MRI scanning (Roelofs et al, 2009). During affect-congruent trials, participants should approach happy faces and avoid angry faces, by pulling a joystick towards themselves or pushing a joystick away, respectively.…”
Section: Methodsmentioning
confidence: 99%